PENGALAMAN DAN TANGGUNG JAWAB AUDITOR SEBAGAI DASAR MENDETEKSI KEKELIRUAN DAN KECURANGAN - Lilik Subagiyo . (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
Abstract Accountant as a professional claiming to apply its professionalism in conducting inspection to financial statement. Accountant also have to apply its deftness of such as those which expressed in common public standard third that or the obligation of. auditor use attention and carefully deftness professionalism in audit and in compilation audit report. Standard make an audit of by explicit claim auditor to give sensible certainty that by mistake error, insincerity and irregularities, fraud, in financial statement having the character of material of  detected. Besides also an accountant in executing inspection duty claimed to have membership and ability. By mistake error, insincerity and irregularities, fraud, meaning indication of is existence of is wrong material saji both for intended and also which is not intended done by individual and also organization Keywords: Error, Insincerity, Irregularities.